Gamifying Assessments in Medical Education: Impact of Gamification on Student’s Test Scores - Madiha Ata; Shazia Irum; Fahad Azam; Abida Shaheen; Shahzad Riyaz; Muhammad Waqas Rabbani (Liaquat National Journal of Primary Care)
Background: Gamification in academic settings is a specific type of Technology Enhanced Assessment (TEA) designed to engage learners in an interactive learning environment and increase motivation. Objective: To explore the role of gamification in improving the academic performance of medical students in Pakistan. Methods: A mixed-methods approach was employed for the present study, which was conducted from March to May 2022. 251 medical students attempted a formative assessment through online platforms with and without gamification. Students were interviewed for the collection of qualitative data. Results: Among the study participants, 54.2% were males and 45.8% were females, with a mean age of 19.26±1.14 years and 20.16±0.96 years in the first and second-year MBBS students respectively. The findings revealed a significant gender difference in test scores between students who used gamified and non-gamified assessment tools. However, the comparison of mean formative assessment scores with and without gamification did not yield statistically significant results. Overall, the students had a good perception of the introduction of gamification in assessment and expressed a desire to experience it more frequently. Conclusion: Gamified assessments can improve academic outcomes by promoting engagement and can mitigate gender disparities in assessment scores. Further research is warranted to explore the specific mechanisms by which gamification influences learning outcomes and to investigate its effectiveness across diverse student populations.